2005
DOI: 10.1007/s11136-004-7711-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life in children with psychiatric disorders

Abstract: Objective: To assess factors that, in addition to childhood psychopathology, are associated with Quality of Life (QoL) in children with psychiatric problems. Methods: In a referred sample of 252 8 to 18-year-olds, information concerning QoL, psychopathology and a broad range of child, parent, and family/ social network factors was obtained from children, parents, teachers and clinicians. Results: Poor child, parent, and clinician reported QoL was associated with child psychopathology, but given the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
75
5
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(100 citation statements)
references
References 41 publications
(57 reference statements)
19
75
5
1
Order By: Relevance
“…This result could be expected because internalizing symptoms are related to an impairment of psychological well-being and quality of life. 32 A correlation between internalizing symptoms and impairment of quality of life was also found by Sawyer et al 25 in a sample of children and adolescents with mental disorders. Considering the effects of asthma severity on quality of life, previous findings have been inconsistent.…”
Section: Asthma and Mental Healthsupporting
confidence: 58%
See 1 more Smart Citation
“…This result could be expected because internalizing symptoms are related to an impairment of psychological well-being and quality of life. 32 A correlation between internalizing symptoms and impairment of quality of life was also found by Sawyer et al 25 in a sample of children and adolescents with mental disorders. Considering the effects of asthma severity on quality of life, previous findings have been inconsistent.…”
Section: Asthma and Mental Healthsupporting
confidence: 58%
“…Besides psychopathology, other factors have been found to impair quality of life, such as social skills or recent stressful life events that were not included in this study. 32 Further studies should also consider these aspects. The need for support was judged by caregivers on a unidimensional scale.…”
Section: Asthma and Mental Healthmentioning
confidence: 99%
“…Other factors which were not measured in the present study might influence the course of a child's QoL. In another study [4], we investigated the association between QoL and child, parent, and family/social network factors and found that several of these factors, especially child and family/social network factors, were associated with QoL. It might be these factors that need to be addressed in QoL specific interventions.…”
Section: ■ Children At Riskmentioning
confidence: 64%
“…In the pediatric age, at a time when chronic disease is less prevalent than later in life, systematic use of this measure in communitybased studies can enable recognition of neglected groups who may be disadvantaged from the perspective of health and social care. [21][22][23][24][25] Children from disadvantaged social groups generally achieve poorer scores regarding both mental health and HRQoL.…”
Section: Discussionmentioning
confidence: 99%